PRODUCTIVITY AND PROFITABILITY OF HDPS COTTON INFLUENCED BY GENOTYPES AND INM PRACTICES - S. TRIVENI and M. YAKADRI, G. VINAY, K. P. VANI, B. PADMAJA, G. JAYASREE (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted at College Farm, Agricultural College, Rajendranagar, Hyderabad, during kharif, 2019-20 and 2020-21 to study effect of genotypes and integrated nutrient management practices on profitability of HDPS cotton. Experiment was laid out in Split plot design, with two genotypes as main plots (M) and nine Integrated Nutrient Management practices as sub plots (S). Among genotypes, higher lint yield (919; 836 kg ha-1), seed yield (1604; 1468 kg ha-1), stalk yield (6412; 6110 kg ha-1), net returns (93929; 88387 ¹ ha-1) and B: C ratio (2.74; 2.72) were obtained by Bt variety (KCH-14 K59 BG II) compared Non-Bt variety (ADB-542) during kharif, 2019-20 and 2020-21, respectively. While, among integrated nutrient management practices, significantly higher lint yield (1157; 1047 kg ha-1), seed yield (1983; 1807 kg ha-1) and stalk yield (7190; 6853 kg ha-1) and net returns (123795; 115397) were observed with 100% RDF + soil application Jeevamrutha @ 500 L ha-1 at 15 days interval up to harvest (S5) during both years and was comparable with 100 % RDF + Foliar spray of Jeevamrutha @ 5% at 15 days interval up to harvest (S7) and 100 % RDF (S3), respectively. However, higher B: C ratio (3.46; 3.49) was obtained with 100% RDF (S3) during both seasons.